The English lexicon mirrors functional brain activation for a sensory hierarchy dominated by vision and audition: Point-counterpoint. (August 2020) - Reilly, Jamie; Flurie, Maurice; Peelle, Jonathan E.
Abstract: Word meanings are often suffused with sensory, motor, and affective features. For many of us, a word such as beach evokes a diverse range of pleasant associations including blue skies (visual), gritty sand (tactile), crashing waves (auditory), and the distinctive smell of sunscreen (olfactory). Aristotle argued for a hierarchy of the senses where vision and audition eclipse the lesser modalities of odor, taste, and touch. A direct test of Aristotle's premise was recently made possible with the establishment of the Lancaster Sensorimotor Norms (2019), a crowdsourced database cataloging sensorimotor salience for nearly 40, 000 English words. Neurosynth, a metanalytic database of functional magnetic resonance imaging studies, can potentially confirm if Aristotle's sensory hierarchy is reflected in functional activation within the human brain. We correlated sensory salience of English words as assessed by subjective ratings of vision, audition, olfaction, touch, and gustation (Lancaster Ratings) with volumes of cortical activation for each of these respective sensory modalities (Neurosynth). English word ratings reflected the following sensory hierarchy: vision > audition > haptic > olfaction ≈ gustation. This linguistic hierarchy nearly perfectly correlated with voxel counts of functional activation maps by each sensory modality (Pearson r = .99). These findings are grossly consistent with Aristotle's hierarchy of the senses. We discuss implications and counterevidence from other natural languages. Highlights: Aristotle proposed a hierarchy of the senses such that vision and audition eclipse smell, taste, and touch. We examined whether this hierarchy is reflected in natural language and in patterns of brain activation. Near perfect correlations exist between sensory ratings of words with functional brain activation for the primary senses. These data suggest that a sensory hierarchy dominated by vision and audition is reflected both in language and brain. Data from other natural languages cast doubt on the universality of this phenomenon.